Sinophone Southeast Asia Sinitic Voices across the Southern Seas - Hoogervorst, Tom; Chia, Caroline (Chinese Overseas, 2021)
This volume explores the diverse linguistic landscape of Southeast Asia's Chinese communities. Based on archival research and previously unpublished linguistic fieldwork, it unearths a wide variety of language histories, linguistic practices, and trajectories of words. The localized and often marginalized voices we bring to the spotlight are quickly disappearing in the wake of standardization and homogenization, yet they tell a story that is uniquely Southeast Asian in its rich hybridity. Our comparative scope and focus on language, analysed in tandem with history and culture, adds a refreshing dimension to the broader field of Sino-Southeast Asian Studies. . Readership: Students, scholars, (academic) libraries, community organizations, heritage organizations; linguistics, Southeast Asia Studies, East Asia Studies, Overseas Chinese